Immune suppression during bovine trypanosomosis - Taylor, K.; Mertens, B.; Rocchi, M.; Elson, L. (OAU/STRC, 2001)
The Development of vaccine against the African trypanosomiasis passes through the identification process of invariant component. This process targets the prevention of infection or diseases related to it. Immunity suppression in almost a universal feature of infection and represents probably an essential element of the host-parasite relationship. To highlight the mechanisms which can reduce the reactions of the specific T. antigen, we have studied the behaviour of the immune cells, including the activation by the cytokines, of a cattle infected by T. congolense. A prolification lymphatic specific trypanosome, as well as a secretion of (SFN-y), can be detected in the lymph node, which drains the site of the infection even before the first peak of parasitism (10-12 days post-infection). However, these reactions drop very rapidly to point zero at day 30 post-infection. This reaction loss of T. specific antigens is concomitant to an increase of the expression of IL-10 mRNA. The transcription of IFNY, of IL-2 is reduced on the contrary. These changes in the transcription of the mRNA of cytokines are also associated with the reduction of the existing monocytes, including nitricoxide (NO), by (IFN-y) or the production of TFNy. In monocyte culture originated from non-infected cattle, IL-10 cuts out the secretion of (NO) and of TNF-y brought by IFNy. The addition of anti-body anti-IL10 in monocytes cultures originated from infected cattle restores partially the secretion of NO, but has no effect on the production of TNF-y. At the end, it is possible that the increment of IL-10 is implicated in the abolition of T-auxillary cells of 1 type and of cytokines inflammatory during the infection. We ignore if the abolition of the reactions protects the cattle of immune pathology or if it interferes with their capability of controlling the addiction.